Corporate social responsibility and innovation performance in Chinese firms with R&D investments as a mediator - Yingxiang, Cheng; Teruki, Neilson; Taasim, Shairil Izwan Bin (Asian Journal of Economic Modelling, 2025)
Motivated by the important role of innovation in firms’ competition and development, this study explores whether Corporate Social Responsibility (CSR) affects firms’ innovation performance. Using a qualitative approach, the relevant literature is reviewed, theoretical analysis is conducted, and hypotheses are developed. The empirical examinations utilize publicly listed Chinese A-share market company data from 2011 to 2020, which contains 23,962 firm-year observations. This study employs double-fixed-effect Ordinary Least Squares (OLS) regression to estimate the baseline model. The results show that CSR positively influences firms' innovation performance, suggesting that CSR activities foster innovation. Subsequently, the study confirms these findings through robustness checks, including alternative measures, periods, and Two-stage OLS regression. Using the Sobel test, the research also examines how R&D investments mediate the relationship between CSR and innovation performance, confirming R&D as a mediator. The findings highlight the critical role of CSR in enhancing firms’ innovation performance. It also emphasizes the importance for policymakers to establish regulations requiring companies to undertake CSR, including economic, social, and environmental responsibilities. Additionally, practitioners should focus more on CSR and foster a CSR culture to improve innovation performance and better meet stakeholder demands.